2020
DOI: 10.1038/s41598-020-76108-z
|View full text |Cite
|
Sign up to set email alerts
|

A physical memristor based Muthuswamy–Chua–Ginoux system

Abstract: In 1976, Leon Chua showed that a thermistor can be modeled as a memristive device. Starting from this statement we designed a circuit that has four circuit elements: a linear passive inductor, a linear passive capacitor, a nonlinear resistor and a thermistor, that is, a nonlinear “locally active” memristor. Thus, the purpose of this work was to use a physical memristor, the thermistor, in a Muthuswamy–Chua chaotic system (circuit) instead of memristor emulators. Such circuit has been modeled by a new three-dim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…Moreover, it can be shown that for all g satisfying ( 11) the EP at the origin has unique unstable eigenvalue (see Appendix). This implies that for each fixed gap g ∈ (g a , g b ), and hence for the value of G a given by (10), there exists a range of g defined by condition (11) where SMCC possesses three EPs and the EP at the origin has a unique unstable eigenvalue. It is worth to remark that this scenario is quite similar to that displayed by the double-scroll family [44].…”
Section: B Nonlinearity Nmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it can be shown that for all g satisfying ( 11) the EP at the origin has unique unstable eigenvalue (see Appendix). This implies that for each fixed gap g ∈ (g a , g b ), and hence for the value of G a given by (10), there exists a range of g defined by condition (11) where SMCC possesses three EPs and the EP at the origin has a unique unstable eigenvalue. It is worth to remark that this scenario is quite similar to that displayed by the double-scroll family [44].…”
Section: B Nonlinearity Nmentioning
confidence: 99%
“…In the volatile case, to obtain oscillations, a passive memristor with an S-type locally active quasi-static i − v characteristic is used. As in a typical Hanson-Pearson oscillator, the memristor is biased via a suitable network in the locally-active region, i.e., in a branch of the characteristic with a negative differential resistance (NDR) [5], [6], [11], [12], [33]. It is worth to remark that NDR is observed in thermistors and other specific types of passive nanoscale devices, as NbO x , VO 2 , and TaO x devices [34].…”
Section: Introductionmentioning
confidence: 99%
“…As a nonlinear locally-active device, S-type LAM is conceptually simple for building oscillating circuit without pure negative resistor, and the local active region renders the oscillating system capable to amplify extermely small fluctuation in energy. Therefore, S-type LAM is preferred over other memristor in the design of chaotic oscillator [35][36][37]. In Ref [30], Wang designed a S-type LAM-based chaotic oscillator by using a resistor, a capacitor and an inductor.…”
Section: Introductionmentioning
confidence: 99%
“…14 There is also a lot of research on building chaotic systems and neural networks based on memristors. [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] For example, in 2008, it was derived that several nonlinear oscillators from Chua's oscillators by replacing Chua's diodes with memristors. 15 In 2012, delayed switching effect was used to control the switching of a memristor synapse between two neurons.…”
Section: ⅰ Introductionmentioning
confidence: 99%
“…25 A physical memristor based on the Muthuswamy-Chua chaotic system (circuit) was provided. 27 In this paper, based on the memristor-based transient chaotic neural network (MTCNN), 31 the chaotic state for a long time is realized by the MTCNN. By MTCNN, AES initial key is dynamically generated to realize "one time one secret."…”
Section: ⅰ Introductionmentioning
confidence: 99%